EDUCATION IN REMOTE ACCESS: A TEACHER’S VIEW - E. E. Ivanova (Вестник университета)
The problems faced by teachers in the conditions of forced transition to distance learning due to the pandemic COVID-19 have been analysed, when interaction with students was carried out only with the use of information technologies. The advantages and disadvantages of organizing training sessions using various educational platforms have been highlighted: Zoom, Microsoft Office 365, Skype. Psychological and pedagogical barriers that affect the perception of educational material by students, the performance of the teacher and student, including the effectiveness of educational interaction between them, have been considered. The problems of organizing and conducting intermediate certification in remote access have been emphasized: difficulties in identifying students ‘ identities, and the use of proctoring technologies.